Dean Mosman letter to Thomas Kent regarding winter bird sightings, February 11, 1981 - Mosman, Deanet al (1981)
A list of birds sighted by Dean Mosman. He notes that he has fewer sightings this year given the mild Winter. This item was used as supporting documentation for the Iowa Ornithologists Union Quarterly field report of winter 1980-1981. Epson - sheet feed/flatbed